(untitled) (Research, Society and Development, 2021)
The present article aims at analyzing aspects that can contribute to an inventory of Popular Education experiences, based on Paulo Freire’s thought, in the historical, political, and economic context of the last years, with more emphasis on the process of re-democratization up to the present time. In the face of the denial of science and of an education that can criticize the events of the current reality, we cannot do without the foundations of Freire’s thought, which defend a critical and popular education as an element of human emancipation. This study is developed from a bibliographical research of a qualitative nature, having in the dialectic the method which is the basis of its analysis. As a result, the foundations of Freire’s thought are recovered through his main experiences and his articulation with the popular struggles of this time. Freire’s process of action and reflection projects viable novelties that inspire new actions and new commitments for all educators, because we cannot go through planetary life without a transforming praxis, at the risk of incurring in a posture of supporting the disastrous directions that the capitalist crisis, in its economic, social, political, cultural, environmental and educational dimensions, is shaping.